Determination of water requirement for alternate wetting and drying irrigation method of lowland rice in Bukidnon - Olila, Nelsa J.; Ang, Roejae Carlo A. (2017)
Irrigation water delivered to the rice fields decreases during dry season causing crop damage due to water shortage. The study aimed to estimate the irrigation water requirement of a one hundred hectare rice fields in Maramag, Bukidnon during the dry season. Parameters of water requirement were collected which include soil properties, weather data, and farming practices. Water discharge at National Irrigation Administration canal and Kibalagon creek that served the area was measured. Water saving technique using alternate wetting and drying was implemented during the dry season cropping and water used was measured using the observation well. The farm delivery requirement is 6.16 lps/ha, thrice the value used in planning irrigation operation activities. AWD saved 39% of the water used compared to conventional irrigation. The results suggests that irrigation water delivered to the area cannot sustain the water requirements, especially during dry season.
Keywords: Irrigation System; Irrigation; Rice field irrigation; Mindanao studies